Cooking for bureaucrats: Why the policy of food reformulation is hard to stomach - Josie Appleton (Institute of Economic Affairs (IEA), 2019)
Under the UK government's policy of 'reformulation', food products are subject to government targets for the reduction of salt, sugar and calories. It puts Public Health England in the position of monitoring and effectively regulating the composition of virtually every part of the prepared food supply, including not only ready-meals and supermarket biscuits but also the recipes of cafés and restaurants. It represents the largest extension of state control over the British diet since rationing. To assist with the reformulation scheme, Public Health England (PHE) has spent nearly a million pounds on food sales data, with the greatest spend (423,452) in the financial year 2018/19. The scheme is highly bureaucratic. Since 2017, there have been 220 different active salt and sugar targets. Proposals for new calorie reduction targets include a baffling range of food products, which most people would not consider to be unhealthy, including: olive ciabatta, boxed salads, sushi, bao buns, vegetable crisps, protein balls, yoghurt covered raisins, croutons, braised cabbage, mushy peas, pesto, hollandaise sauce, quinoa (with additions), spelt and barley (with additions), guacamole, pease pudding, and prepared salads. Many of the targets are surreal, such as the recommendation that sweets should contain less than 50 per cent sugar, when boiled sweets are almost solely made up of sugar; or the request that fudge, made from sugar and butter/cream, should decrease the sugar content without increasing the fat content. The guideline for sugar content in nut butters is less than that naturally occurring in cashew nuts. The guideline calories for olive bread is lower than that of a plain baguette or ciabatta. The guideline target for crisps and nuts is 403kcal per 100g, whereas plain peanuts contain 600kcal per 100g. Reformulation has been driven less by nutritional science, or public demand, than by the concerns of an out-of-touch state bureaucracy. This bureaucracy has entered into a mutually beneficial alliance with single issue pressure groups such as Action on Sugar and the Obesity Health Alliance, which call for reformulation to be backed up with sanctions. Action on Sugar and PHE exchange e-mails almost every week, and seem to meet in person around once a month. Policies are run past the pressure groups in their early stages, and only released to the food industry for consultation much later. Food reformulation is an irrational bureaucratic standard which will detach the food market from the tastes, preferences and nutritional goals of consumers. The danger is that food products will be designed, not primarily to please the public, but to meet the arbitrary and often illogical targets that are set by health bureaucrats. The scheme is likely to result in a decline in taste, value for money and possibly also in nutritional quality.
Keywords: 330